Factors Controlling the Diels–Alder Reactivity of Hetero‐1, 3‐Butadienes. Issue 12 (26th November 2018) - Yu, Song; de Bruijn, Hans M.; Svatunek, Dennis; Hamlin, Trevor A.; Bickelhaupt, F. Matthias
Abstract: We have quantum chemically explored the Diels–Alder reactivities of a systematic series of hetero‐1, 3‐butadienes with ethylene by using density functional theory at the BP86/TZ2P level. Activation strain analyses provided physical insight into the factors controlling the relative cycloaddition reactivity of aza‐ and oxa‐1, 3‐butadienes. We find that dienes with a terminal heteroatom, such as 2‐propen‐1‐imine (NCCC) or acrolein (OCCC), are less reactive than the archetypal 1, 3‐butadiene (CCCC ), primarily owing to weaker orbital interactions between the more electronegative heteroatoms with ethylene. Thus, the addition of a second heteroatom at the other terminal position (NCCN andOCCO ) further reduces the reactivity. However, the introduction of a nitrogen atom in the backbone (CNCC ) leads to enhanced reactivity, owing to less Pauli repulsion resulting from polarization of the diene HOMO inCNCC towards the nitrogen atom and away from the terminal carbon atom. The Diels–Alder reactions of ethenyl‐diazene (NNCC) and 1, 3‐diaza‐butadiene (NCNC ), which contain heteroatoms at both the terminal and backbone positions, are much more reactive due to less activation strain compared toCCCC . Abstract : Go forth and cyclize ! A comprehensive account detailing the reactivity of a series of aza‐ and oxa‐dienes in hetero‐Diels–Alder reactions with ethylene is presented. The combined activation strain and energy decomposition analyses elucidate the factors governing reaction rates and highlight the delicate interplay between orbital interactions and strain, depending on the position of the heteroatom.